Metal-Based Nanoparticles and the Immune System: Activation, Inflammation, and Potential Applications. (1st June 2015) - Luo, Yueh-Hsia; Chang, Louis W.; Lin, Pinpin
Abstract : Nanomaterials, including metal-based nanoparticles, are used for various biological and medical applications. However, metals affect immune functions in many animal species including humans. Different physical and chemical properties induce different cellular responses, such as cellular uptake and intracellular biodistribution, leading to the different immune responses. The goals of this review are to summarize and discuss the innate and adaptive immune responses triggered by metal-based nanoparticles in a variety of immune system models.